Modification Of Tamarind Seed Starch With Octenyl Succinic Anhydrate (Osa) In The Production Of Mayonnaise - Sidek, Siti Shafinaz Mohd (Universiti Sains Malaysia, 2020)
Egg yolk contains lecithin which has emulsifying ability to produce mayonnaise but contains high cholesterols which is not preferable by consumer. Tamarind seed starch (TSS) is an underutilize and cheap resources make it a suitable substitute for egg yolk as an emulsifier. The objective of this study is to study the effect of acid hydrolysis pre-treatment and octenyl succinate anhydride (OSA) modification on emulsifying properties of TSS and further analysis in the production of mayonnaise. Pre-treatment with acid hydrolysis were conducted prior to OSA modification. Four samples, NT (native TSS), AT (acid treated TSS), OST (OSA modified TSS) and AOST (acid treated with OSA modified TSS) were analysed their emulsifying properties. In the mayonnaise production, four ratios egg yolk to AOST were used M0 (100:0), M25 (75:25), M75 (25:75) and M100 (0:100). High DS value upon dual modification of TSS give high emulsifying properties of starch. All emulsions exhibit shear thinning behaviour (n < 1, pseudoplastic). AOST showed highest apparent viscosity and emulsion index (EI) values and microscopic analysis showed small size of oil droplets compared to the others. Hence, AOST were chosen to further proceed with mayonnaise production. All mayonnaise was found to exhibit shear thinning behaviour (n < 1, pseudoplastic) with M25 showed highest apparent viscosity. M0 presented highest EI values, pH value and lowest creaming and thermal creaming index followed by M25, M75 and M100. All samples showed significantly different value of L*, a* and b*. Droplets were closely packed with homogenous small size of oil droplets was clearly observed in M25. From all the results, M25 had shown to be the best emulsifying ability because various mechanism such as steric stabilization and granules interaction.